Analisis Mitigasi Risiko Pembiayaan Rahn di BMT NU Jatim Cabang Klampis Bangkalan - Luk Lu’us Syarifah; Farid Ardyansyah; Trischa Relanda Putra (CV. Global Cendekia Inti, 2026)
Rahn financing in Islamic microfinance institutions is exposed to various risks that may affect institutional operational stability, including financing risk, operational risk, liquidity risk, and Sharia compliance risk. This study aims to analyze the risk mitigation strategies implemented in rahn financing at BMT NU East Java, Klampis Branch, Bangkalan. The study is motivated by the need for effective risk management to maintain financing quality and minimize the occurrence of non-performing financing. This research employed a qualitative approach using a case study method. Data were collected through interviews, observations, and documentation and analyzed using the Miles and Huberman model, which consists of data reduction, data display, and conclusion drawing. The analysis was further supported by NVivo 12 Pro software to facilitate systematic data coding and categorization. The findings indicate that the primary risks in rahn financing include financing risk (credit risk), operational risk, liquidity risk, and Sharia compliance risk. Risk mitigation efforts are carried out through the implementation of the 5C+1S principles (Character, Capacity, Capital, Collateral, Condition of Economy, and Sharia Compliance), conservative collateral valuation, periodic monitoring, and a persuasive family-oriented approach. Collateral execution is applied as a last resort in resolving non-performing financing. These strategies have proven effective in reducing risks and maintaining institutional stability. The study also reveals that social and family-based approaches constitute a distinctive characteristic of risk mitigation practices in BMTs as Islamic microfinance institutions.